2004, the year in the balance : a special report - Bruce, Robert (Balance sheet ;, 2004)
One of the key issues of the year is a simple one. Across Europe all listed companies will have to carry out their financial reporting under the rules promulgated by the International Accounting Standards Board by the year 2005. This means that 2004, given that comparative figures will have to be shown in 2005, is the crunch time. But it is not only Europe. Countries right around the world have latched onto the initiative and are following suit. The question is how far this movement towards harmonizing global financial reporting can move. The stumbling block, like so much in the business world, is the US. The US financial reporting standard-setting body is committed to convergence, but this initiative has to overcome the sharp divide between the USA and much of the rest of the world. The US favors a mass of rules allowing as little judgment as possible while the rest of the world favors principles rather than rules, finding that business works better if people can use their judgment.